Unveiling the diversity of Eutichurus Simon, 1897 (Araneae: Cheiracanthiidae) in Colombia: new species, records and comments on their distribution - Casas, Cristian M.; Villarreal-Blanco, Eduardo; Morales, Adriana; Osorio, Carlos; Martínez, Leonel (Zootaxa, 2025)
The taxonomic knowledge of Eutichurus Simon, 1897 in Colombia, currently represented by eight species, is increased with the description of six new species: Eutichurus luisdiazi sp. nov. (♂♀), Eutichurus tibacuy sp. nov. (♂♀), Eutichurus meta sp. nov. (♂♀), Eutichurus yariguies sp. nov. (♀), Eutichurus muisca sp. nov (♂), and Eutichurus andresgarcia sp. nov (♂). In addition, new morphological data are provided for Eutichurus arnoi Bonaldo, 1994, whose male is described for the first time. Furthermore, the first accurate locality record for E. cumbia Bonaldo & Ramírez, 2018 in Tabio, Cundinamarca is presented. New records from Colombia are also provided for Eutichurus marquesae Bonaldo, 1994, Eutichurus tropicus (L. Koch, 1866) and Eutichurus valderramai Bonaldo, 1994. We provide an updated taxonomic key and new distribution maps for all the species included in this study, as well as new photographic documentation for several species previously known to occur in Colombia (E. arnoi, E. cumbia, E. putus O. Pickard-Cambridge, 1898, E. tropicus, E. marquesae, and E. valderramai). Additionally, specimens of E. putus, E. sigillatus Chickering, 1937 and E. furcifer, from non-Colombian localities, are photographed here for the first time, accompanied by comments regarding their geographic distribution. With the new species proposed herein, the genus is now represented by 14 species in the country.